Local authorities and the social determinants of health - Bonner, Adrian (Bristol : Policy Press, 2020)
As many social inequalities widen, this is a crucial survey of local authorities' evolving role in health, social care and wellbeing. Health and social and public policy experts review structural changes in provision and procurement, and explore social determinants of health including intergenerational needs and housing. With detailed assessments of regional disparities and case studies of effective strategies and interventions from local authorities, this collaborative study addresses complex issues (Wicked Issues), considers where responsibility for wellbeing lies and points the way to future policy-making. The Centre for Partnering (CfP) is a key outcome of this innovative review along with Bonner's previous work Social Determinants of Health (2017).
Title from publisher's bibliographic system (viewed on 26 Mar 2021).
Keywords: Medical policy -- Great Britain; Local government -- Great Britain